Nipping the dead mall trend in the bud: a modified shopper-based mall equity model for South Africa's distressed malls - Asphat Muposhi; Chengedzai Mafini; Roy Marlon Shamhuyenhanzva (Inderscience, 2023)
A modified shopper-based mall equity model was applied to gain insights into possible strategies to reposition distressed shopping malls in South Africa. Mall-intercept and online survey were used to collect cross-sectional data from 623 shoppers recruited from 15 distressed malls. Structural equation modelling was employed for hypotheses testing. Mall awareness and mall environment emerged as significant predictors of shopping mall value attributed to distressed malls. The effect of shopping mall personality on shopping mall value was insignificant, while perceived mall difference had a negative effect. The path from shopping mall value to mall attachment was also insignificant. Demalling, mall renovation and a distinctive mall personality are suggested as potential strategies to reposition distressed malls and keep pace with experiential value accorded by internet-based malls. Mall personality may be improved by shifting away from a cost-oriented strategy by embracing a differentiated mall strategy premised on enhancing shopper experiential value.